The Students’ Attitude Towards The Use of Interactive Classroom Activities in Developing The Communicative Competence of the Eleventh Grade Students of SMA Kristen Barana - Roni La’biran; Resnita Dewi; Muthmainnah Muthmainnah; Muhammad Hasby (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2018)
The objective of the research is to find out the students’ attitude toward the use of interactive classroom activities in developing the communicative competence. The researchers used descriptive method with a questionnaire to obtain data. The variable of the research was independent variable referring to the use of interactive classroom activities and dependent variable was the students’ attitude. The population of this research was the eleventh grade students of the SMA Kriten Barana’ Academic year 2017/2018, which consists of 50 students since the population of this research, used random sampling. The data obtained from the questionnaire tabulated and analyzed using percentage technique. It is provided by the students’ option on all items of the questionnaire where the number of students who strongly agree and agree is greater than those disagree and strong disagree. in this research the eleventh grade students of SMA Krenten Barana’ have positive attitude towards the use of interactive classroom activities in developing their communicative competence.